Empowering Cireng Small Business In Tandes Village, Surabaya - Rao, Leonard Alfredo Da Costa; Tan, Clarita Christy; Tifany, Keisya; Kriswanto, Devoria Adelline; Menny, Mario Rosindo (PT. Amirul Bangun Bangsa, 2024)
The research sets out to address three central challenges plaguing the cireng MSMEs. Firstly, it delves into the presence of outdated production processes, examining traditional methods and the lack of access to modern technology that compromises both the quality and quantity of cireng production. Secondly, the study explores suboptimal branding and marketing strategies employed by local entrepreneurs, such as Ms. Ana's cireng business, aiming to refine these approaches for increased market reach. Lastly, the research aims to overcome the geographical limitations hindering businesses from extending their reach beyond immediate boundaries. The research methodology employs a comprehensive situational analysis approach, involving detailed identification of challenges, examination of market dynamics, mapping of production processes, and critical evaluation of branding and marketing strategies. This method provides a holistic understanding of the hurdles faced by cireng MSMEs, serving as a foundation for targeted and impactful interventions. The findings underscore the interconnected challenges faced by cireng MSMEs in Tandes Village, highlighting the significance of addressing outdated production processes, refining branding and marketing strategies, and overcoming geographical limitations. The community engagement project, guided by the research, is strategically poised to drive positive and sustainable change, offering a pathway to enhanced productivity, sustainable growth, and increased prosperity for the local MSMEs.